Investigation of the genotoxic effect and trace element levels of the nickel-titanium arc-wires used in orthodontic treatment - Erdem, Onur; Şimsek Çetinkaya, Şahika; Kaplan, M.; Çırak, Eyüp; Gökçe, Sıla Mermut; Akay, Cemal (Elsevier Ireland Ltd, 2016)
Nickel-titanium alloy arch-wires are the most frequently used biomaterials thanks to their biocompatibility in orthodontic treatment. Despite these properties we have some evidence about carcinogenic, mutagenic and cytotoxic effects of the materials is associated with their corrosion properties. In this study, we aimed to investigate the genotoxic effects using Micronucleus (MN) technique in 32 patients (consisting of 16 boys and 16 girls whose ages range from 12 to 17) undergoing the Ni-Ti arc-wires treatment. Also, some bioelement (Fe, Cu and Zn) levels in saliva were determined for certain sampling times. The sampling time for patients is 0 (as control) 7th, 15th, 30th, 45th, 60th and 90th days. The mean MN frequency per 1000 cells has increased significantly in days 7, 15, 30 and 45 compared to the control group. However, there was not a significant difference between the 60th and the control group. In addition, the mean MN frequency in the 90th day was found to decrease significantly compared to the control group. Cu values in the saliva samples showed a statistically significant increase in all experimental groups compared to the control group, while there was a significant decrease in Fe and Zn values compared to the control group. Consequently, it has been determined that the genotoxic effects related to Ni-Ti alloy wire were at identifiable levels; however, these effects did not pose a problem in terms of the long-term biocompatibility of the materials.
52nd Congress of the European-Societies-of-Toxicology (EUROTOX) -- SEP 04-07, 2016 -- Seville, SPAIN
WOS: 000402436700891
Keywords: Toxicology; Orthodontics; Dentistry